The LARC (Language Acquisition Resource Center) Program - Kenefick, Barbara; Paznik, Jane; Center for Urban Education, New York, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
The purpose of the LARC (Language Acquisition Resource Center) project is to implement a home-based program which will help children of ages six months to five years develop communication skills. The program is designed for children of all socioeconomic groups, although it has been set up by the Center for Urban Education (CUE) as a pilot program with children of inner city or ghetto backgrounds. It can be administered by a parent or parent surrogate in the home or in a home setting, or by a specially trained language counselor. The LARC program as it now exists has been piloted for a one-year period in an inner city housing project of a medium-sized eastern city. CUE proposes to generate and test in a field setting all materials of instruction in both the home curriculum and the training course used in the program, along with various measures of language acquisition skills that can be achieved by children at different stages of development. Results achieved so far indicate that the LARC program is valuable as a solution to pressing educational problems now being addressed by schools and communities. (Author/RB)
Educational level discussed: Early Childhood Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Language; Communication Skills; Disadvantaged Youth; Early Childhood Education; Inner City; Language Acquisition; Language Skills; Parent Participation; Preschool Children; Program Descriptions; Language Acquisition Resource Center NY